2008
DOI: 10.1183/09031936.00023708
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal infection in the rabbit impairs post-natal growth and lung alveolarisation

Abstract: Clinical and experimental studies indicate an association between chorioamnionitis and bronchopulmonary dysplasia in preterm infants. The present authors hypothesised that, in the rabbit, antenatal infection may impair lung development after birth, despite effective maternal antibiotic therapy.Pregnant rabbits received an intra-uterine inoculation of 10 3 Escherichia coli colony forming units or vehicle at the end of gestation (day 29). Intravenous ceftriaxone therapy was initiated 8 h after inoculation for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Disrupted lung development has been demonstrated in animal models of chorioamnionitis (9,20,44,61,68), but other experimental studies showed that intra-amniotic inflammatory stimuli do not necessarily impair lung structure when assessed later during infancy (43,47). It has been suggested that the postnatal environment may interact with antenatal inflammation to further worsen late respiratory outcomes of preterm infants exposed to chorioamnionitis.…”
mentioning
confidence: 99%
“…Disrupted lung development has been demonstrated in animal models of chorioamnionitis (9,20,44,61,68), but other experimental studies showed that intra-amniotic inflammatory stimuli do not necessarily impair lung structure when assessed later during infancy (43,47). It has been suggested that the postnatal environment may interact with antenatal inflammation to further worsen late respiratory outcomes of preterm infants exposed to chorioamnionitis.…”
mentioning
confidence: 99%
“…In addition, reciprocal chromosome painting using human chromosomes showed complete homology in more than three chromosomes (7). Based on these observations, a rabbit seems to be a more appropriate model compared with other classical animal models for studying human lung development and various gene expressions during intrauterine and early neonatal life (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…However, the experimental studies on rabbits (animal model which resembles most the humans by chronological development of the alveoli) showed that untreated infection led to decreased respiratory alveolar surface (by 25%), leukomalacia, and postnatal retarded growth (by 60%) [14,15].…”
Section: Volume 3 • Number 2 • May 2016 • Hophmentioning
confidence: 99%
“…Th is may provide a window for pre-venting the white matter damage [14,25,26]. Screening for asymptomatic bacteriuria and treatment is recommended for selected groups such as pregnant women, where benefi t has been shown [2,3].…”
Section: Volume 3 • Number 2 • May 2016 • Hophmentioning
confidence: 99%